Proceedings of the International Conference of CELSciTech 2019 - Science and Technology Track (ICCELST-ST 2019) 2019
DOI: 10.2991/iccelst-st-19.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Design and Manufacturing of Organic Rankine Cycle (ORC) System Using R-134a as Working Fluid with Solar Collector as Source Energy

Abstract: Renewable energy sources such as solar heat, wind energy, geothermal, biomass and exhaust heat is one way to overcome the crisis of energy and environment in the world. Organic Rankine Cycle (ORC) is a power generation system modified from Rankine Cycle by using organic liquid with low boiling point as working fluids such as R-134a, therefore various types of heat sources can be use. This research was design and manufacture organic Rankine cycle by using R-134a as working fluid with solar collector as the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The R-134a, as a standard refrigerant in refrigeration systems, is attracting attention as a potential option at low temperatures such as 95ºC [10] [11]. However, the high-pressure aspect of R-134a indicates that system design must consider this aspect carefully [12]. R-11, with its low boiling point at atmospheric pressure, shows promising thermodynamic properties at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The R-134a, as a standard refrigerant in refrigeration systems, is attracting attention as a potential option at low temperatures such as 95ºC [10] [11]. However, the high-pressure aspect of R-134a indicates that system design must consider this aspect carefully [12]. R-11, with its low boiling point at atmospheric pressure, shows promising thermodynamic properties at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Naibaho et al, [26] designed a helical type evaporator and condenser and a flat plate collector as a solar heat absorber, and found that the ORC system produced 0.305 kW of electrical energy and 4.3% thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%